Overview of thyroid gland characteristics in pregnancy using ultrasonography as an assessment tool - Agrawal, Alka; Shukla, Prachi; Taya, Silky (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Thyroid gland is one of the most common gland affected during pregnancy as it responds to the increased physiological demands of iodine and energy during pregnancy. Any thyroid dysfunction can result in abortion, preterm labor or affects fetal neurodevelopment. Various anthropometric factors or genetic factors apart from iodine intake are known to affect the size of thyroid gland. Changes in thyroid gland morphology can be easily measured using ultrasonography as clinically the enlargement can be labelled as goiter. In this review, we aimed to evaluate the changes in thyroid gland during pregnancy and assess the different factors affecting its size across the various studies as the literature data concerning the thyroid gland enlargement during pregnancy is controversial. Various articles on thyroid volume changes during pregnancy from literature were reviewed along with a cross-sectional observation done in a government hospital setup in India, on 240 patients who were divided into 4 groups of 60 patients each which included non-pregnant females in group 1 and pregnant females in all three trimesters respectively in the rest 3 groups. Thyroid gland morphology and its characteristics such as volume, nodularity, echogenicity and vascularity were measured using high frequency ultrasonography in each group and then compared. Thyroid volume in the third trimester group (7.24±1.16 ml) was found to be significantly greater (p<0.001) than in the non-pregnant group (5.44±0.82 ml). BMI was found to be the highest in third trimester group as expected. Even in iodine sufficient areas we found thyroid gland volume to increase during pregnancy from non-pregnant group along with thyroid gland nodularity. Vascularity assessed based on CDFS pattern shows pattern I to be most common. Variation in thyroid gland characteristics between pregnant and non-pregnant controls was found.